A Novel HNF4A Mutation Causing Three Phenotypic Forms of Glucose Dysregulation in a Family - Chandran, Suresh; Rajadurai, Victor Samuel; Hoi, Wai Han; Flanagan, Sarah E.; Hussain, Khalid; Yap, Fabian (Frontiers in Pediatrics, 2020)
Maturity-onset diabetes of the young (MODY) classically describes dominantly inherited forms of monogenic diabetes diagnosed before 25 years of age due to pancreatic β-cell dysfunction. In contrast, mutations in certain MODY genes can also present with transient or persistent hyperinsulinemic hypoglycemia in newborn infants, reflecting instead β-cell dysregulation. Of the MODY genes described to date, only hepatocyte nuclear factor-4-alpha (HNF4A; MODY1) and hepatocyte nuclear factor -1- alpha (HNF1A; MODY3) mutations may result in a biphasic phenotype of hypoglycemia in early life and hyperglycemia in later life. We report a family with a novel HNF4A mutation with diverse phenotypic presentations of glucose dysregulation. The proband was a term, appropriate-for-gestational age male infant with symptomatic hypoglycemia on day 3 of life needing high glucose infusion rate to maintain normoglycemia. He was born to a non-obese and non-diabetic mother. Glucose regulation was optimized using diazoxide upon confirmation of hyperinsulinism. Cascade genetic screening identified the same mutation in his father and elder sister, but mother was negative. Father was diagnosed with Type 1 diabetes at 15 years of age that required insulin therapy. Proband’s elder sister, born at term appropriate for gestational age, presented with transient neonatal hypoglycemia needing parenteral glucose infusion for a week followed by spontaneous resolution. The paternal grandparents were negative for this mutation, confirming a paternal de novo mutation and autosomal dominant inheritance in this family. This pedigree suggests that the presence of early-onset paternal diabetes should prompt molecular testing in infants presenting in the newborn period with diazoxide-responsive hyperinsulinemic hypoglycemia, even in the absence of maternal diabetes and macrosomia.